Pemberian makanan F100 dengan bahan substitusi tepung tempe terhadap status protein pasien anak dengan gizi kurang - Diniyah Kholidah; Endy Paryanto Prawirohartono; Fatma Zuhrotun Nisa (Jurnal Gizi Klinik Indonesia, 2013)
Background: Much effort has been made to counter the weaknesses of F100 through the development of milk powder substituted with ingredients that have a high content of protein and energy, high bioavailability and relatively low cost.Objective: To analyze an effect of F100 supplementation using substitute tempeh flour on protein status (total protein serum and serum albumin) among undernourished pediatric patients.Method: Experimental research with randomized clinical control trial among 30 undernourished children consisting of open clinical trial in two experiment groups, supplemented with F100 or substitute F100 (isoenergetic and isoprotein diet) within 14 days. The study was undertaken in April-August 2010 at pediatric inpatient room of Dr. Saiful Anwar Hospital Malang. Data of food intake were obtained through visual Comstock and 24-hour food recall; data of total serum protein through biuret method; serum albumin (Alb) through cellulose acetate electrophoresis method. Data analysis was using Pearson Chi-Square test and unpaired t-test.Results: The result of unpaired t-test on the average intake of energy, protein, fat and carbohydrate showed there was no significant difference in each experimental groups (p>0.05). The test result of total serum protein level and serum Alb level showed there was no significant difference in each experiment (p=0.240 and p=0.774). The result of correlation coefficient test showed there was no significant association between intake of energy and nutrient and total serum level and serum Alb level (p>0.05) and degree of association showed a weak association (r>0.25).Conclusion: Formula of F100 substitute as complementary food could be used as an alternative food in diet therapy of malnourished children on rehabilitation phase.